Learning SPARQL : querying and updating with SPARQL 1.1 - DuCharme, Bob (O'Reilly Media, 2013)
Gain hands-on experience with SPARQL, the RDF query language that's bringing new possibilities to semantic web, linked data, and big data projects. This updated and expanded edition shows you how to use SPARQL 1.1 with a variety of tools to retrieve, manipulate, and federate data from the public web as well as from private sources. Author Bob DuCharme has you writing simple queries right away before providing background on how SPARQL fits into RDF technologies. Using short examples that you can run yourself with open source software, you'll learn how to update, add to, and delete data in RDF datasets. Get the big picture on RDF, linked data, and the semantic web; Use SPARQL to find bad data and create new data from existing data; Use datatype metadata and functions in your queries; Learn techniques and tools to help your queries run more efficiently; Use RDF Schemas and OWL ontologies to extend the power of your queries; Discover the roles that SPARQL can play in your applications.